Peran Guru Bimbingan dan Konseling melalui Layanan Bimbingan Klasikal untuk mengurangi Kenakalan Remaja - Ilham Aziz Aryoso; Mudaim Mudaim; Hadi Pranoto (Universitas Muhammadiyah Metro, 2025)
The purpose of this study was to determine the profile of juvenile delinquency committed by students and the role of teachers in providing advice to students in reducing juvenile delinquency through classical guidance at SMK Muhammadiyah 2 Metro. This study used a descriptive methodology. The method of collecting information in this exploration is a subjective explanation strategy through observation and interviews. The instruments used in this exam are observation and interview guidelines. The results of the examination can be summarized as follows: (1) The types of juvenile delinquency committed by students are absenteeism, smoking, being late and going to the thermos during teaching and learning activities. (2) The stages of implementing classical guidance services consist of three stages, namely: initial/initial stage, implementation stage, and closing/assessment stage. (3) Through the implementation of classical guidance services, students actually want to reduce juvenile delinquency by improving their way of behaving, the desire to change is accompanied by the ability of students to reduce juvenile delinquency by choosing good associations with this also having a good impact on student behavior and mentality